Bi-Interfacial Electron Modulation in Co9S8/FeCoS2 Heterostructures Anchored on Bamboo-Derived Carbon Quasi-Aerogel for High-Performance Hydrogen Evolution - Wenjing He; Jianliang Cao; Xinliang Zhou; Ning Zhang; Yuzhu Qi; Jin Li; Naiteng Wu; Xianming Liu (Gels)
Hydrogen energy as a sustainable alternative to fossil fuels necessitates the development of cost-effective and efficient electrocatalysts for the hydrogen evolution reaction (HER). While transition metal sulfides have shown promise, their practical application is hindered by insufficient active sites, poor conductivity, and suboptimal hydrogen adsorption kinetics. Herein, we present a heterointerface engineering strategy to construct Co9S8/FeCoS2 heterojunctions anchored on bamboo fiber-derived nitrogen-doped porous carbon (Co9S8/FeCoS2/BFPC) through hydrothermal synthesis and subsequent carbonization. BFPC carbon quasi-aerogel support not only offers a high surface area and conductive pathways but also enables uniform dispersion of active sites through nitrogen doping, which simultaneously optimizes electron transfer and mass transport. Experimental results demonstrate exceptional HER performance in alkaline media, achieving a low overpotential of 86.6 mV at 10 mA cm−2, a Tafel slope of 68.87 mV dec−1, and remarkable stability over 73 h of continuous operation. This work highlights the dual advantages of heterointerface design and carbon substrate functionalization, providing a scalable template for developing noble metal-free electrocatalysts for energy conversion technologies.